EFEKTIVITAS DISCOVERY LEARNING BERBANTUAN PhET SIMULATION TERHADAP HASIL BELAJAR KOGNITIF GERAK LURUS - Febiola Yewi; Indah Slamet Budiarti; Putu Victoria M. Risamasu (Journal of Education Papua Baru, 2023)
Abstract: This study aims to describe the improvement and difference in students' cognitive learning outcomes when taught using the Discovery Learning model assisted by PhET Simulation media compared to the conventional model on the topic of Linear Motion. A quantitative quasi-experimental approach was applied using a Nonequivalent Control Group Design. The research subjects consisted of 27 students in the experimental class (XI F2) and 26 students in the control class (XI F5) at SMA YPPK Asisi Sentani, selected through a cluster random sampling technique. The primary instrument for data collection was a 30-item multiple-choice objective test. Data analysis was performed digitally, encompassing the N-gain test, classic assumption prerequisite tests, and hypothesis testing via the Independent Sample T-Test. The results indicated that the average N-gain score of the experimental class reached 0.64 (medium category), whereas the control class only reached 0.27 (low category). The t-test yielded a Sig. (2-tailed) value of 0.000 (< 0.05), proving a highly significant difference in learning improvement. In conclusion, the Discovery Learning model through PhET Simulation media is empirically effective in improving students' cognitive learning outcomes in physics. Keywords: Discovery Learning, PhET Simulation, Linear Motion, Learning Outcomes. Abstrak: Penelitian ini bertujuan mendeskripsikan peningkatan dan perbedaan hasil belajar kognitif peserta didik yang diajarkan menggunakan model Discovery Learning berbantuan media PhET Simulation dibandingkan dengan model konvensional pada materi Gerak Lurus. Pendekatan kuantitatif eksperimen semu (quasi-experimental) diterapkan menggunakan rancangan Nonequivalent Control Group Design. Subjek penelitian terdiri atas 27 siswa kelas eksperimen (XI F2) dan 26 siswa kelas kontrol (XI F5) di SMA YPPK Asisi Sentani yang dipilih melalui teknik cluster random sampling. Instrumen utama pengumpulan data berupa tes objektif pilihan ganda sebanyak 30 butir soal. Analisis data dilakukan secara digital mencakup uji N-gain, uji prasyarat asumsi klasik, dan pengujian hipotesis melalui Independent Sample T-Test. Hasil analisis menunjukkan skor rata-rata N-gain kelas eksperimen mencapai 0,64 (kategori sedang) dan kelas kontrol hanya 0,27 (kategori rendah). Uji-t menghasilkan nilai Sig. (2-tailed) sebesar 0,000 (< 0,05), yang membuktikan adanya perbedaan peningkatan yang sangat signifikan. Kesimpulannya, model Discovery Learning melalui media PhET Simulation secara empiris efektif meningkatkan hasil belajar kognitif fisika peserta didik. Kata kunci: Discovery Learning, PhET Simulation, Gerak Lurus, Hasil Belajar.